Understanding the Effectiveness of Demonstration Programs. (1st March 2015) - Price, Allison; Boeving, Emily R.; Shender, Marisa A.; Ross, Stephen R.
Abstract: This project sought to understand guest engagement during great ape demonstrations conducted at the Regenstein Center for African Apes in the Lincoln Park Zoo. We were interested in how these demonstrations engaged audiences, relative to a non-demonstration-viewing experience, as well as how they compared to each other. In 2012 and 2013, we conducted 336 visitor surveys, collecting data before and directly following both the research and training demonstrations, to measure knowledge gain and affective change. We also compared visitor responses to assess potential variances in the ability of these demonstrations to affect both knowledge and attitude shifts about apes. Preliminary results indicated that the presence of either demonstration program enhanced the visitor's knowledge and caring attitudes; however, there was no significant difference between the two program types. In sum, these results demonstrated the capability of interpreted demonstrations in a zoo setting and the relative ability of research- and husbandry-themed programs to engage audiences. These were critical reflections for us as we embarked on a new research- themed exhibit on zoo grounds.